2010
DOI: 10.1111/j.1467-8535.2008.00914.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of older and younger adults' attitudes towards and abilities with computers: Implications for training and learning

Abstract: Computers and associated technology have become central to modern life. In a society where the population is rapidly ageing, the acceptance and utilisation of developing technologies by an older population is becoming increasingly important. This review highlights similarities and differences between the attitudes and acceptance of technology by older and younger people, leading to the conclusion that similar factors influence both age groups-hence, older people could well be taught to use technology in a simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
145
3
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(166 citation statements)
references
References 42 publications
13
145
3
5
Order By: Relevance
“…Despite age differences, there was no difference between digital modalities in emotional connections to artefacts Age was not an influential factor in experiencing emotional responses to either the 3D models on a laptop modality or the AR on a tablet modality shown outside of a museum. Past studies have shown differences between older and younger people and their technology backgrounds and skills (Olson et al 2011;Broady et al 2010) and our participants had a significantly different number of museum visits (see Table 2); therefore it was surprising that for many of the variables, our findings showed no significant differences between these two age groups across the digital modalities.…”
Section: Discussioncontrasting
confidence: 52%
“…Despite age differences, there was no difference between digital modalities in emotional connections to artefacts Age was not an influential factor in experiencing emotional responses to either the 3D models on a laptop modality or the AR on a tablet modality shown outside of a museum. Past studies have shown differences between older and younger people and their technology backgrounds and skills (Olson et al 2011;Broady et al 2010) and our participants had a significantly different number of museum visits (see Table 2); therefore it was surprising that for many of the variables, our findings showed no significant differences between these two age groups across the digital modalities.…”
Section: Discussioncontrasting
confidence: 52%
“…In making this observation we do not mean to restate the old and undemonstrated stereotype that older adults are technologically inadequate or intrinsically reluctant to learn or use technologies. In fact, in their literature review on older and younger adults' attitudes towards computers, Broady, Chan, and Caputi (2010) found that ''the negative stereotypes of older people being avoidant of technology and incapable of its use are outdated'' (p. 483) and that younger and older adults have quite similar attitudes towards and experiences of using technologies. However, Broady et al found that, in technology-enhanced education addressed to older learners, the designers should give those learners more time so they can master new skills; they should also take care to provide them support as they learn to use technology so they feel comfortable and successful.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies about age and learning have shown that even though some cognitive degradation occurs with age, the ability and desire to learn of older people are not significantly different from younger people when the learning is specifically changed to address their slower learning rate and need for positive reinforcement (Broady, Chan, & Caputi, 2010). Broady, Chan, & Caputi (2010) showed that recent training and positive experiences could efficiently counteract the challenges of cognitive losses due to age.…”
Section: Analyzing the Evidencementioning
confidence: 99%
“…Broady, Chan, & Caputi (2010) showed that recent training and positive experiences could efficiently counteract the challenges of cognitive losses due to age.…”
Section: Analyzing the Evidencementioning
confidence: 99%